2017
DOI: 10.3233/rnn-160708
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-specific effects of repetitive magnetic stimulation on primary astrocyte cultures

Abstract: Our results provide preliminary evidence that rMS can influence astrocyte physiology, indicating the potential for a novel mechanism by which rTMS can influence brain activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
2
21
1
Order By: Relevance
“…Thus, our stimulation protocol likely induced action potentials in some pyramidal neurons, mostly in the superficial layers of the cortex, but did not directly activate thalamic neurons. However, E-field values below the threshold value required to produce action potentials have been observed inducing non-synaptic mechanisms of neuroplasticity such as structural reoganisation (Makowiecki et al, 2014), increased neurogenesis (Heath et al, 2018), gene regulation and increased intracellular calcium (Grehl et al, 2015;Clarke et al, 2017b), altered neuron excitability (Tang et al, 2016;Makowiecki et al, 2018), and glial changes (Clarke et al, 2017a;Cullen et al, 2019). Therefore, we cannot rule out that non-synaptic mechanisms of plasticity induced in the thalamus by low intensity magnetic fields may contribute to the changes in firing parameters that we report here.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, our stimulation protocol likely induced action potentials in some pyramidal neurons, mostly in the superficial layers of the cortex, but did not directly activate thalamic neurons. However, E-field values below the threshold value required to produce action potentials have been observed inducing non-synaptic mechanisms of neuroplasticity such as structural reoganisation (Makowiecki et al, 2014), increased neurogenesis (Heath et al, 2018), gene regulation and increased intracellular calcium (Grehl et al, 2015;Clarke et al, 2017b), altered neuron excitability (Tang et al, 2016;Makowiecki et al, 2018), and glial changes (Clarke et al, 2017a;Cullen et al, 2019). Therefore, we cannot rule out that non-synaptic mechanisms of plasticity induced in the thalamus by low intensity magnetic fields may contribute to the changes in firing parameters that we report here.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, astrocytes regulate several neuronal protective mechanisms known to be modulated by rTMS (Becerra‐Calixto & Cardona‐GĂłmez, 2017). Despite this, so far, few studies have explored the impact of rTMS on glial cells, being the existing data inconclusive (Clarke et al., 2017). Reports from pre‐clinical models indicate that HF‐rTMS induce astrocyte activation (Chan et al., 1999; Raus et al., 2013) and proliferation (Medina‐Fernandez et al., 2017), but also that it has no effect (CzĂ©h et al., 2002; Kim et al., 2013; Sasso et al., 2016; Yang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed using two-way ANOVA followed by Bonferroni's post hoc test. **p < 0.01 and ***p < 0.01 compared to control; ##p < 0.01 compared to OGD/R; $$$p < 0.001 compared to control HF-rMS (Clarke et al, 2017). Reports from pre-clinical models indicate that HF-rTMS induce astrocyte activation (Chan et al, 1999;Raus et al, 2013) and proliferation (Medina-Fernandez et al, 2017), but also that it has no effect (CzĂ©h et al, 2002;Kim et al, 2013;Sasso et al, 2016;Yang et al, 2018).…”
Section: F I G U R Ementioning
confidence: 98%
“…Studies assessing the influence of EMF on ATP signaling and intra- and extracellular Ca 2+ in astrocytes are scarce, have been made with extremely low frequency magnetic fields (ELF-MF) and ELF-EMF, respectively (34,85), and look at in vitro astrocyte cultures. However, computational models that studied the influence of EEG field on calcium waves in the neocortex (39) do suggest potential effects of ELF-MF, ELF-EMF, and EEG on ATP signaling and extracellular Ca 2+ concentration in astrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…While Clarke et al (85) have shown that ELF-MFs increase intracellular calcium levels within the cytoplasm of the cultured astrocytes, Golfert et al (34), by studying microvesicle motility of astrocytes in in vitro cultures, have also suggested that ELF-EMFs change calcium levels by increasing calcium influx. Increased Ca 2+ ion influx is usually a product of astrocytic induction of diffusion of IP3 through gap junctions and extracellular ATP signaling and, in normal conditions, it activates the surrounding microglial cells and changes astrocytes’ morphology and mobility.…”
Section: Resultsmentioning
confidence: 99%